Estudo de viabilidade econômica de um projeto de captação de águas pluviais para fins não potáveis de uma instituição de ensino no município de Itapejara D’Oeste - PR - Ribas, Luidy Henrique Couto (2025)
Water is an essential resource for the survival of humanity on the planet, playing a fundamental role in quality of life and environmental balance. However, the growing water scarcity due to climate change, population growth, and poor distribution of resources has led to a global crisis, affecting both arid countries and regions with high water availability, such as Brazil. Despite holding 11% of the world's fresh water, Brazil faces challenges in the distribution of this resource, particularly in the southern and southeastern regions, where there is high demand and limited availability. In this context, certain actions can be implemented in buildings facing issues related to poorly distributed rainfall, flooding, or droughts. Therefore, this study aims at conducting an economic feasibility analysis for the implementation of a rainwater harvesting system for non-potable purposes at a public educational institution at Itapejara d’Oeste, Paraná. Precipitation data from the nearest weather station to the school were obtained, along with data related to the catchment areas and locations for the implementation of system components through the architectural project. Additionally, information about the population involved and the routines for the use of potable and non-potable water were collected to determine the institution’s demands. With this information and the assistance of AutoCAD software, all system elements were sized and specified, including the lower and upper storage reservoirs, which were designed using the Netuno Software (version 4). All components and services related to the implementation were budgeted using the SINAPI table to Paraná state, updated in November 2024. Costs related to electricity and sanitation services were also obtained from the responsible agencies, taking into account taxes and inflation. Subsequently, the lifting system was dimensioned based on tables and characteristic curves, with final data entered into the Netuno software interface, which, along with the budgeted components and services, conducted the economic analysis of implementing the system at the referred institution.